Respuestas

2013-08-27T05:49:34+02:00
7x -12 = 3x +4
7x -3x = 4 + 12
4x = 16
x = 16/4
x =4

7x-12 = 3(x+14)
7x - 12 = 3x + 42
7x- 3x = 42 +12
4x = 54
x = 54/4

3/4x+5 = 11
3/4x = 11-5
3/4x = 6
3x = 4(6)
3x = 24
x =24/3
x =8

2/5x-8=12
2/5x = 12+8
2/5x = 20 
2x = 5(20)
2x =100
x =100/2 
x = 50

7/6x=x+3
7x = 6 (x + 3 )
7x = 6x + 18
7x - 6x = 18
1x =18
x =18

2/3x -1 = 5
2/3x = 5 + 1
2/3x = 6
2x = 3 (6)
2x = 18
x = 18/2
x =9
 

2(x-5) = x - 4
2x - 10 = x - 4
2x - x =10 - 4
2x - x = 6
x = 6


3(x+6) = 2(x+8)
3x + 18 = 2x + 16
3x- 2x = 16 -18
1x = -2
x = -2


3(x-1)+x = 13
3x - 3 + x = 13
4x = 13 + 3
4x = 16
x = 16/4
x = 4

x-2(x+1)  = 7- 4x
x - 2x - 2 = 7 - 4x
x - 2x + 4x = 7 + 2
3x = 9
x =  9/3
x = 3


4/9(3-x)+x=8
12 - 4x 
----------- + x = 8
  9

12 - 4x + 9x 
------------------- = 8
          9
12 - 4x + 9x = 8 (9)
12 + 5x = 72
5x = 72 - 12
5x = 60
x = 60/5 
x = 12

2/3x+6=3/4(x-2)+7
2/3x + 6 =  3x - 6 
                ---------- + 7
                   4
2/3x +6 =  3x -6 +28
               ---------------------
                       4
2/3x + 6 = 3x + 22
                --------------
                      4
2/3x + 6 =  3 ( 3x +22)
                    --------------
                         4
2/3x +6 =  9x + 66
                --------------
                     4
4 (2/3x+ 6 ) = 9x +66
8/3x + 24 =  9x + 66
8/3x = 9x +66 - 24
8/3x = 9x +42
8/x = 3(9x + 42)
8X = 27x + 126
8x - 27x = 126 
- 21x = 126
x = - 126/21
x = - 6